Response of Bone Resorption Markers to Aristolochia longa Intake by Algerian Breast Cancer Postmenopausal Women - Bachir Benarba; Boumedienne Meddah; Aicha Tir Touil (Advances in Pharmacological Sciences)
Aristolochia longa is widely used in traditional medicine in Algeria to treat breast cancer. The aim of the present study was to investigate the response of bone resorption markers to A. longa intake by Algerian breast cancer postmenopausal women. According to the A. longa intake, breast cancer patients were grouped into A. longa group (Al) (n=54) and non-A. longa group (non-Al) (n=24). 32 women constituted the control group. Bone resorption markers (from urine) pyridinoline (PYD) and deoxypyridinoline (DPD) were determined by HPLC. Serum and urinary creatinine, uric acid, and urea were measured. 1 g of A. longa intake resulted in significant rise of renal serum markers and a pronounced increase of bone resorption markers. The intake of A. longa roots is detrimental for kidney function and resulted in high bone resorption, maybe due to the reduction in renal function caused by the aristolochic acids contained in the roots.